2022
DOI: 10.1097/qai.0000000000002832
|View full text |Cite
|
Sign up to set email alerts
|

HIV Disease Dynamics and Markers of Inflammation and CNS Injury During Primary HIV Infection and Their Relationship to Cognitive Performance

Abstract: Introduction:Early systemic and central nervous system viral replication and inflammation may affect brain integrity in people with HIV, leading to chronic cognitive symptoms not fully reversed by antiretroviral therapy (ART). This study examined associations between cognitive performance and markers of CNS injury associated with acute HIV infection and ART.Methods:HIV-infected MSM and transgender women (average age: 27 years and education: 13 years) enrolled within 100 days from the estimated date of detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
7
2
Order By: Relevance
“…Lower levels of Aβ42 and Aβ40 in CSF and plasma and decreases in those levels are associated with AD, cognitive decline, and psychiatric and behavioral symptoms in aging individuals without HIV . Some studies have reported no association with either plasma Aβ42 or Aβ40 levels in PLWH, specifically men who have sex with men and transgender women …”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Lower levels of Aβ42 and Aβ40 in CSF and plasma and decreases in those levels are associated with AD, cognitive decline, and psychiatric and behavioral symptoms in aging individuals without HIV . Some studies have reported no association with either plasma Aβ42 or Aβ40 levels in PLWH, specifically men who have sex with men and transgender women …”
Section: Discussioncontrasting
confidence: 63%
“…HIV crosses the blood-brain barrier, activates microglia, and leads to neuroinflammation and neurodegeneration, resulting in the release of NFL . Published studies in cross-sectional samples of PLWH have reported higher NFL levels in association with lower NP, and no association between baseline levels of NFL and subsequent cognitive decline over 24 months or more in PLWH, including men who have sex with men and transgender women . Some reports indicate that impaired kidney function, more commonly observed among PLWH, may be associated with changes in blood NFL levels .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 216 randomized participants, all participants with plasma biomarkers assessed at baseline or longitudinally through 24 weeks were included in this subanalysis. Participants were selected for biomarker analysis if they were co-enrolled in a related observational study that evaluated neurologic or reservoir outcomes [ 16 , 17 ], had near-complete samples at the selected timepoints, and started ART at the designated visit (either at enrollment in the immediate arm or at week 24 in the deferred arm).…”
Section: Methodsmentioning
confidence: 99%
“…HIV-1 enters the brain during the first initial weeks of acute infection (17)(18)(19)(20) via transmigration of HIV-1 infected cells across the blood-brain barrier (BBB) (21)(22)(23). In the periphery, HIV-1 targets the CD4 + T cells and monocytes that then disseminate infection to other tissues and organs (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%